Who is blaming the baby?. Issue 5 (21st August 2009) - Peters, C; Becher, J C; Lyon, A J; Midgley, P C
Abstract : Sudden unexplained collapse within the first 12 h of life is a rare but recognised event. Over a 2-year period, five infants, previously assessed as healthy, were found collapsed in our maternity unit in the care of their primiparous mothers. Two were found prone on their mother's chest, and two were in their mother's bed. The outcomes were poor, with four neonatal deaths and one death at 18 months. The rate of sudden unexplained neonatal collapse was 0.4 per 1000 live births. No cause for collapse was identified despite extensive investigations, which included postmortem in all the neonatal deaths. One infant, however, showed widespread antenatal brain damage at postmortem. It is postulated that some infants with an underlying vulnerability may maladapt to extrauterine life following an hypoxic stressor possibly caused by positional airway obstruction.